Draft Annual Plan 1993-94 Government of Gujarat - Planning Commission (Planning Commission, 1992)
The agricultural year 1992-93 can be considered as satisfactory to some extent. The State is expected to harvest 35.98 lakh tonnes of foodgrains in kharif season. In the case of oilseeds, the production groundnut is likely to be affected because of practically no rains after the first week of September m most of the groundnut growing areas. The production of groundnut is expected to be nearly about 15.00 lakh tonnes The production of cotton is likely to be 17.88 lakh bales, 170 kgs. each.
Government of Gujarat, General Administration Department Planning Division